До історії села Ведильці Чернігівського району - Рослий, І. (Сiверянський лiтопис, 2015)
Перші поселення на горбистих берегах річки, згодом названої р. Пакулькою, лівого притоку р. Дніпра, з’явилися в XVI-XVII столітті. В історичних документах назва села «Деревня Виделци» згадувалась уже в 1619 р. як об`єднання хуторських поселень: Дворец, Старосілля, Малосілля, Рословка та ін. У 1730 р. населення села складалося з 159 монастирських селян, а до 1924 р. поступово збільшилося до 2768 людини, об`єднаних в одноосібних господарствах. З кількох версій походження сучасної назви більш вірогідною є: від назви гори «Відельци», де в XVIII столітті була збудована церква, навколо якої продовжувало розбудовуватися село з успішними землеробством, тваринництвом, різноманітними сільськогосподарськими ремеслами. Під час колективізації тридцятих років ХХ століття заможні одноосібні господарства були ліквідовані та організовані два колгоспи. Первые поселения на холмистых берегах реки, со временем названой р. Пакулькой, левого притока р. Днепра, появились в XVI-XVII столетиях. В исторических документах название села «Деревня Видельци» упоминалось уже в 1619 г. как объединение хуторских поселений – Дворец, Староселье, Малоселье, Рословка и др. В 1730 г. население села составляло 159 монастырских крестьян, а до 1924 г. постепенно увеличилось до 2768 человек, содержащие единоличные хозяйства. Среди нескольких версий происхождения современного названия села более вероятной следует считать – от названия горы «Видельцы», на которой в XVIII столетии построена церковь, а вблизи ее продолжало застраиваться село с успешными земледелиями, животноводством, разнообразными сельскохозяйственными ремеслами. Во время коллективизации сельского хозяйства 30-х годов ХХ столетия зажиточные единоличные хозяйства были ликвидированы, организовано два колхоза. The first settlements on the hills of the river later called Pakulka, left tributary of the Dnieper river, were built in the 16th-17th centuries. Historical sources tell that the name of the village ‘Videltsy village’ was mentioned as early as 1619 as an association of farm-steads, namely: Dvorets, Staroselie, Maloselie, Roslovka and others. There are several hypothesis explaining the etymology of the modern name of the village, beginning from the ancient «Palace of Kiev-Pechersk Lavra Monastery» dated back to 1729, the most probable one being derivative from the name of the mountain ‘Videltsy’, on which in the 18th century a church was built where about a village started building on with successful farming, cattle-breeding, various agricultural occupations developing. In 1730, the population of the village was 159 of monastery farmers. In 1755–1769 as many as 87 village families had 55 horses, 94 oxen, 151 cows, 245 sheep, 25 goats, 55 pigs in their households. The 18th and 19th centuries for the village were marked by active development of individual handicraft trades. From 1859 to 1928 as many as 39 handicraftsmen possessed 25 windmills and watermills, 10 hulling mills, 7 oil mills, 2 brickworks, 2 smithies. Building, carpentry, timberwork, weaving and clothing manufacture were widely developed. By the begining of the 20th century 2319 dessiatinas of fertile plough-lands were cultivated, so, together with pastures, the village possessed 3065 dessiatinas of land. Out of 2768 village residents only 379 people were considered poor, the rest were mainly prosperous peasants. During collectivization of the thirties in the 20th century, prosperous individual farms were liquidated, and two collective farms were organized instead.